High-Resolution Spectroscopy of Asymmetric Top Molecules in Non-Singlet Electronic States: ν1 + ν3 Band of the ClO2 Molecule; Optics and Spectroscopy; Vol. 130, iss. 7 - Bekhtereva E. S. Elena Sergeevna; Kakaulin A. N. Aleksey Nikolaevich; Merkulova M. A. Maria Andreevna; Gromova O. V. Olga Vasilievna; Konova Yu. V. Yuliya Vladimirovna; Sydow Ch. Christian (2022, 2022)
Title screen